Implementasi Konsep Exploring Local History Experience pada Perancangan Interior Museum Kota Samarinda - Grace Shella Sulistio; Ronald Hasudungan Irianto Sitinjak; Linggajaya Suryanata (Intra, 2018)
The identity of Samarinda society can be understood by its history and culture. However, there is not any public space to preserve this heritage. Indeed, there is a mini-museum named Galeri Samarinda Bahari, but the gallery is not representative because it has small space. Therefore, the interior design of Samarinda city museum with conservative, informative, educative, recreational, innovative and interactive approach is necessary. The design method includes assimilation and general study. Assimilation stage consists of discovery and point of view. General study stage includes planning, analyzing and problem-solving. The conservative values are presented through the design that takes on the characteristic of Jepen Tepian Olah Bebaya traditional dance. The informative and educative values are presented through the information distribution about museum collection which is grouped based on the historical chronological order of Samarinda City. “Exploring Local History Experiences” concept was expected to make visitors can explore, enjoy, and learn about history in eight zones with a different atmosphere. Meanwhile, recreative, innovative, and interactive values are presented through self-service activities showroom supported by the latest technology. By achieving these values, Museum of Samarinda City is expected to preserve the local history and culture. In addition, Samarinda can be a new tourist destination that worth to visit and recognized by the public.